Financial Performance and Sustainability of Microfinance Institutions in Morocco: A Structural Equation Model - Chedad, Khawla; Boukir, Ayoub; Chaabi, Sanae; Aguenaou, Samir; Abrache, Jawad (International Journal of Economics and Financial Issues, 2022)
The following contribution investigates the main determinants that impact the financial performance and sutainability of Moroccan microfinance institutions (MFIs) in terms of governance indicators, staff productivity variables, and loans portfolio quality. Using an unbalanced panel data extracted from the Mix Market database and using structural equation modeling, 10 Moroccan MFIs were analyzed for the period between 1999 and 2017. Results indicate that there is no evidence of the impact of the regulatory environment and portfolio quality on these institutions' profitability, which is represented by the return on assets (ROA) and return on equity (ROE), and sustainability, which is represented by the operational self-sufficiency (OSS) and the number of active borrowers. However, results indicate that personnel productivity has a significant positive direct impact on both profitability and sustainability. This study provides guidance to policy makers in terms of enhancing the performance of personnel productivity of these institutions in the Moroccan context.